Phraseology in El Trajumán by M. Papo (1884) - Olímpio de Oliveira Silva, Maria Eugênia (2020)
The paper analyses a Judeo-Spanish publication, The TraJumán, published in Vienna by Michael Papo, from the point of view of Phraseology as a linguistic subdiscipline. Our aim here is to establish the relation of the Judeo-Spanish phraseological units (PhU) of the publication dealt with here with those of Spanish in general and with the elements borrowed from other languages or loan translations. For this purpose, we carried out a detailed analysis in order to determine, study and classify the PhU according to Corpas’ model (1996), with certain conceptual adaptations (Penadés 2012, López Simó 2016, Núñez Bayo 2016). From a quantitative perspective, the main results of our study, regarding idioms and formulaic expressions, seem to indicate, the existence of a greater number of idioms, as opposed to formulaic expressions. From a qualitative perspective, the study shows (1) the presence of PhU of Spanish in general, (2) the presence of phraseologisms that can be considered formal variants of general Spanish (some of them contain lexical elements borrowed from other languages and have to be mentioned apart) and (3) the existence of some PhU that seem to be loan translations from German or French.